Higher education for all : from challenges to novel technology-enhanced solutions : first International Workshop on Social, Semantic, Adaptive and Gamification Techniques and Technologies for Distance Learning, HEFA 2017, Maceió, Brazil, March 20-24, 2017, Revised selected papers /: from challenges to novel technology-enhanced solutions : first International Workshop on Social, Semantic, Adaptive and Gamification Techniques and Technologies for Distance Learning, HEFA 2017, Maceió, Brazil, March 20-24, 2017, Revised selected papers. (2018) - Unknown
No abstract available